Dispatch of Firefighters and Police Officers in Out‐of‐Hospital Cardiac Arrest: A Nationwide Prospective Cohort Trial Using Propensity Score Analysis. Issue 10 (4th October 2017) - Hasselqvist‐Ax, Ingela; Nordberg, Per; Herlitz, Johan; Svensson, Leif; Jonsson, Martin; Lindqvist, Jonny; Ringh, Mattias; Claesson, Andreas; Björklund, Johan; Andersson, Jan‐Otto; Ericson, Caroline; Lindblad, Pär; et al.
Abstract : Background: Dispatch of basic life support–trained first responders equipped with automated external defibrillators in addition to advanced life support–trained emergency medical services personnel in out‐of‐hospital cardiac arrest (OHCA) has, in some minor cohort studies, been associated with improved survival. The aim of this study was to evaluate the association between basic life support plus advanced life support response and survival in OHCA at a national level. Methods and Results: This prospective cohort study was conducted from January 1, 2012, to December 31, 2014. People who experienced OHCA in 9 Swedish counties covered by basic life support plus advanced life support response were compared with a propensity‐matched contemporary control group of people who experienced OHCA in 12 counties where only emergency medical services was dispatched, providing advanced life support. Primary outcome was survival to 30 days. The analytic sample consisted of 2786 pairs (n=5572) derived from the total cohort of 7308 complete cases. The median time from emergency call to arrival of emergency medical services or first responder was 9 minutes in the intervention group versus 10 minutes in the controls ( P <0.001). The proportion of patients admitted alive to the hospital after resuscitation was 31.4% (875/2786) in the intervention group versus 24.9% (694/2786) in the controls (conditional odds ratio, 1.40; 95% confidence interval, 1.24–1.57). Thirty‐day survival was 9.5% (266/2786) in the intervention group versus 7.7% (214/2786) in the controls (conditional odds ratio, 1.27; 95% confidence interval, 1.05–1.54). Conclusions: In this nationwide interventional trial, using propensity score matching, dispatch of first responders in addition to emergency medical services in OHCA was associated with a moderate, but significant, increase in 30‐day survival. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02184468.